2010
DOI: 10.1128/jb.01628-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofChlamydia trachomatisOuter Membrane Complex Proteins by Differential Proteomics

Abstract: The extracellular chlamydial infectious particle, or elementary body (EB), is enveloped by an intra-and intermolecular cysteine cross-linked protein shell called the chlamydial outer membrane complex (COMC). A few abundant proteins, including the major outer membrane protein and cysteine-rich proteins (OmcA and OmcB), constitute the overwhelming majority of COMC proteins. The identification of less-abundant COMC proteins has been complicated by limitations of proteomic methodologies and the contamination of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 77 publications
6
69
1
Order By: Relevance
“…Proteomic studies (40)(41)(42) have also identified aminoacyl-tRNA synthetases in EBs. Since growth of HS1 was rescued when this mutant was shifted from 40°C to 37°C as late as 18 hpi (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic studies (40)(41)(42) have also identified aminoacyl-tRNA synthetases in EBs. Since growth of HS1 was rescued when this mutant was shifted from 40°C to 37°C as late as 18 hpi (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By analogy, we hypothesize that the osmotically fragile cell membrane of RBs must reorganize during development to form the rigid, highly disulfide crosslinked surface of EBs (35,36). OmcB, OmcC, MOMP, and a large family of polymorphic membrane proteins, constitute the bulk of the Chlamydia outer membrane complex, a proteinaceous shell that provides structural integrity to the outer envelope of EBs (37,38). OmcB and OmcC are developmentally regulated with maximum transcription and translation occurring late in the infectious cycle as RBs begin to transition to EBs (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The intermolecular network at the outer membrane is called chlamydial outer membrane complex (COMC) and is thought to substitute for the very limited amount of chlamydial cell wall peptidoglycan, a component that provides rigidity and structural strength against osmotic pressure to the wall of Gram‐negative bacteria 22. The major constituents of COMC are MOMP and two cysteine rich proteins OmcA and OmcB 25, 26. MOMP is part of the outer shell of two distinct chlamydial life‐cycle manifestations: (1) elementary bodies (EB), which are non‐replicating but infectious and (2) reticulate bodies (RB) which are the non‐infectious, metabolically active, replicating form of the bacteria.…”
Section: Introductionmentioning
confidence: 99%